RESILIENCE AND RECOVERY IN AMERICAN SĀMOA: A CASE STUDY OF THE 2009 SOUTH PACIFIC TSUNAMI. Issue 7 (September 2014) - Binder, Sherri Brokopp; Baker, Charlene K.; Mayer, John; O'Donnell, Clifford R.
<x xml:space="preserve">Abstract</x> Case study methodology was used to explore the culturally situated response and recovery efforts following a tsunami in American Sāmoa. Data indicated that cultural mechanisms were effective in meeting physical needs but insufficient to manage the emotional trauma caused by such a large‐scale event. Samoan cultural norms strongly discourage uncontrolled emotional expression outside of ritualized grieving events. Disruptions in social networks and activities, combined with a lack of available emotional support, resulted in significant psychological distress for many survivors. Sixteen months after the tsunami residents continued to exhibit numerous symptoms of posttraumatic stress. In response to this need for emotional support, some groups within American Sāmoa are setting an example of how their culture can adapt by forging new, culturally grounded methods for addressing emotional needs that arose in the wake of the tsunami. Findings are analyzed through the lens of the social support deterioration deterrence model and activity settings theory.